2009
DOI: 10.1080/10790268.2009.11760758
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Pseudomeningocele Causing Hydronephrosis

Abstract: Background/Objective: Pseudomeningocele is most commonly the result of a rent in the meninges during spine surgery. Noniatrogenic causes exist but are rare. Pseudomeningoceles may heal spontaneously, but they may also slowly enlarge. They rarely present as a mass within the abdomen. The objective of this study was to present the first case report of hydronephrosis secondary to lumbar pseudomeningocele. Design: Single case report and literature review. Methods: Single case report. Results: This man had undergon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Iatrogenic pseudomeningoceles may grow slowly, but generally, they extend into the spinal canal along the neural structures or into the soft tissues toward the surgical incision. Hamilton et al [3] have reported a case of atypical retroperitoneal extension of a pseudomeningocele causing hydronephrosis; however, the cyst developed into the soft tissues through a partial vertebrectomy in a patient who had several complex spinal surgical procedures at the same level. Intravertebral development of CSF cyst has only been described once in the literature by Dhaliwal et al [4]; in their case, the C4 level cyst was diagnosed perioperatively; it involved the posterior arch of the vertebra and was causing partial spinal stenosis.…”
Section: Discussionmentioning
confidence: 97%
“…Iatrogenic pseudomeningoceles may grow slowly, but generally, they extend into the spinal canal along the neural structures or into the soft tissues toward the surgical incision. Hamilton et al [3] have reported a case of atypical retroperitoneal extension of a pseudomeningocele causing hydronephrosis; however, the cyst developed into the soft tissues through a partial vertebrectomy in a patient who had several complex spinal surgical procedures at the same level. Intravertebral development of CSF cyst has only been described once in the literature by Dhaliwal et al [4]; in their case, the C4 level cyst was diagnosed perioperatively; it involved the posterior arch of the vertebra and was causing partial spinal stenosis.…”
Section: Discussionmentioning
confidence: 97%
“…Giant pseudomeningocele is a pathology where the size of the lesion is ≥ 8 cm in diameter (9). It is a very rare entity and only 22 cases have been reported in literature so far (10)(11)(12)(13)(14). MRI is the gold standard for diagnosis of a pseudomeningocele.…”
Section: Casementioning
confidence: 99%